Research on Skin-Friction Drag Reduction by Hydrogen Injection in Supersonic Boundary Layer (Xibei Gongye Daxue Xuebao, 2019)
In order to investigate the applicability of the skin-friction reduction technique using hydrogen injecting into turbulent boundary layer, three-dimensional numerical simulation was carried out for a constant-cross-confined-space with rearward facing steps. The flow characteristics near wall surface and development of wall shear stress were analyzed and compared under different coming flow and injection conditions. The simulation results show that the hydrogen injection can achieve around 13.5% skin-friction drag reduction under the coming flow Mach number of 2.3Ma or 2.8Ma. At 2.8Ma, the optimal reduction profit is 13.5% which is obtained when the equivalent ratio is 0.06. The gases mixings are gradually enhanced along the flow path. At the positions of shock wave-boundary-layer interactions, the mixings are first strengthened and then suppressed, and meanwhile, the wall shear stress and density changes with similar law that first decreases and then rebounds at the positions. The declines of skin-friction drag decrease along the flow direction, the best reduction area can profit nearly 60%.